Suboptimal maize spacing undermines yields and diminishes land utility in Malawi - Kachala, Bertha; Kumwenda, Stella; Matumba, Annie; Mnthambala, Frank; Jere, Zondiwe Mabilabo; Thadzi, Andrew; Kamundi, Elija; Nakoma-Ngoma, Theresa; Chaima, Evance; Kamwamba-Mtethiwa, Jean; Kankwamba, Henry; Ngwira, Amos; et al. (Frontiers in Sustainable Food Systems, 2025)
Intensifying maize production to maximize yields in sub-Saharan Africa, particularly through improved plant spacing, has been governmental policy in many locations for several decades, yet field-level adoption of government recommendations remains uneven. In Malawi, where smallholder maize farming underpins national food security, plant spacing recommendations were introduced in the 1990s to reduce persistent yield gaps. We assessed 240 farms in six agro-ecologically diverse districts in the country to evaluate adherence to the national agronomic guidelines. Field measurements revealed that less than 10% of farms had the recommended plant population of 53,333 plants per hectare, with many falling short by 25% or more. Widespread deviations were driven by excessively wide ridge and intra-row spacing, and by the practice of planting multiple seeds per station (a single sowing point within the row), which introduces intra-station competition and limits yield potential. These findings suggest that adoption of recommended plant spacing options for maize may be limited not only by constraints other than maximizing yield, e.g., labor required for ridge construction, rotation with wider-spaced crops, such as tobacco, and limited access to mechanization, but also by informational gaps regarding their benefits and feasibility. Transitioning to improved spacing through mechanization is financially feasible, even at smallholder scale, and could unlock yield increases of up to 25%. The results observed are consistent with persistent challenges across sub-Saharan Africa, where land scarcity and low-input strategies dominate smallholder agriculture. Addressing agronomic inefficiencies through labor-saving technologies and adaptive policy support is critical to advancing sustainable intensification in the region.